IκB, NF-κB Regulation Model: Simulation Analysis of Small Number of Molecules. (24th January 2008) - Sarkar, Anamika; Meila, Marina; Franza, Robert B.
Abstract : The regulation of Iκ B, NF-κ B is of foremost interest in biology as the transcription factor NF-κ B has multiple target genes. We have modeled a previously published model by Hoffmann et al. (2002) of Iκ B, NF-κ B mathematically as discrete reaction systems. We have used stochastic algorithm to compare the results when there are large and small numbers of molecules available in a finite volume for each protein. Our results for small number of molecules show that with continuous presence of stimulation, nuclear NF-κ B oscillates continuously in every individual cell rather than damping, which was observed in cell population results. This characteristic of the system is missed when averaged behavior is studied.